2014
DOI: 10.1111/1469-0691.12456
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of clinical Aeromonas dhakensis and Aeromonas hydrophila isolates in southern Taiwan: A. dhakensis is more predominant and virulent

Abstract: Aeromonas dhakensis, often phenotypically identified as Aeromonas hydrophila, is an important human pathogen. The present study aimed to compare the clinical and biological features of A. dhakensis and A. hydrophila isolates from human wounds. A total of 80 Aeromonas wound isolates collected between January 2004 and April 2011 were analysed. The species was identified by the DNA sequence matching of rpoD and gyrB (or rpoB if necessary). Most of the Aeromonas isolates were identified as A. dhakensis (37, 46.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 27 publications
7
78
0
Order By: Relevance
“…The expected genus-characteristic resistance against ampicillin was observed for our A. dhakensis strain. Also the results obtained for the susceptibility analysis of the rest of the antimicrobials tested agreed with those reported by other authors, showing that the cephalo sporins (third and fourth generation), monobactams, carbapenems, aminoglycosides, fluoroquinolones, sulphonamides, polypeptides and amphenicols tes ted were highly effective against this microorganism (Figueras et al 2009, Esteve et al 2012, Wu et al 2012, Chen et al 2013, Morinaga et al 2013.…”
Section: A Rivuli Cect 7518 T (Fj969433)supporting
confidence: 89%
See 3 more Smart Citations
“…The expected genus-characteristic resistance against ampicillin was observed for our A. dhakensis strain. Also the results obtained for the susceptibility analysis of the rest of the antimicrobials tested agreed with those reported by other authors, showing that the cephalo sporins (third and fourth generation), monobactams, carbapenems, aminoglycosides, fluoroquinolones, sulphonamides, polypeptides and amphenicols tes ted were highly effective against this microorganism (Figueras et al 2009, Esteve et al 2012, Wu et al 2012, Chen et al 2013, Morinaga et al 2013.…”
Section: A Rivuli Cect 7518 T (Fj969433)supporting
confidence: 89%
“…In our case, pathologic and bac teriologic examination revealed an acute haemorrhagic-necrotizing pneumonia and sepsis associated with A. dhakensis, which was recovered in pure culture from lung, liver, spleen, kidney and blood. Virulence genes detected in our strain (GMV-704), like the alt, aer, lip and ser genes, have been previously recor ded with variable prevalence (27− 100%) in A. dhakensis isolates (Fi gue ras et al 2009, Puthucheary et al 2012, Chen et al 2013, Morinaga et al 2013). The fact that the A. dhakensis GMV-704 strain showed β-haemolysis on sheep blood agar and possessed the aer and lip genes implicated in the production of 72…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…dhakensis and A. aquariorum represented the same taxon (11,12). Although accurate identification of Aeromonas species could be achieved using the nucleotide sequences of housekeeping genes (7,10), these molecular methods are labor-intensive and timeconsuming. Recently, several studies have shown that the matrixassisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) can rapidly and accurately identify different Aeromonas species (13)(14)(15).…”
mentioning
confidence: 99%